Understanding decision-making in cardiac imaging: determinants of appropriate use. (30th November 2017) - Fonseca, Ricardo; Jose, Kim; Marwick, Thomas H
Abstract: Aims: Appropriate Use Criteria (AUC) for echocardiography were developed in 2007 to facilitate decision-making, reduce variability in test utilization, and encourage rational use of imaging. However, there is little evidence that the AUC have favourably influenced ordering behaviour. This study explores the factors that contribute to clinicians requesting echocardiograms with a focus on appropriate use. Methods and results: Semi-structured face-to-face interviews with cardiologists and non-cardiologists who had requested echocardiograms were conducted at an Australian tertiary hospital. The interview guide included hypothetical clinical scenarios to better understand decision-making in ordering echocardiograms and the actions they could take when receiving test reports. Interviews underwent thematic analysis. Seventeen clinicians were interviewed, ten of whom were cardiologists. All participants ordered echocardiograms to support their clinical decision-making. Awareness of the AUC was low. The categorization of tests as 'appropriate' or 'inappropriate' was considered ineffective as it failed to reflect the decision-making process. The decision to request echocardiograms was influenced by a number of personal and systemic factors as well as guidelines and protocols. Training and experience, patients' expectations, and management of uncertainty were key personal factors. Systemic factors involved the accessibility of services and health insurance status of the patient. Conclusion: Factors that influenced the ordering of echocardiograms by clinicians at a tertiary care hospital did not appear to be amenable to control with AUC. Alternative approaches may be more effective than the AUC in addressing the overuse of echocardiography.